BIOLOGIC DRUG PREFERENCES OF TURKISH RHEUMATOLOGISTS IN SPONDILOARTROPATHY PATIENTS WITH ADVANCED CHRONIC RENAL DISEASE - Mercan, R.; Tezcan, M. E.; Yagiz, B.; Ates, A.; Kucuksahin, O.; Bilge, N. S. Yasar; Kalyoncu, U. (Elsevier, 2022)
[Abstract Not Available]
Annual European Congress of Rheumatology (EULAR) -- JUN 01-04, 2022 -- Copenhagen, DENMARK